Clean manufacturing of nanocellulose-reinforced hydrophobic flexible substrates - Dias, Otavio Augusto Titton; Konar, Samir; Leão, Alcides Lopes [UNESP]; Yang, Weimin; Tjong, Jimi; Jaffer, Shaffiq; Cui, Teng; Filleter, Tobin; Sain, Mohini (Elsevier, 2021)
In this study, for the first time, a flexible substrate made from nanofibrillated cellulose in slurry form was fabricated using a hydrophobic polymer base. Previous studies practiced energy-intensive dry cellulose nanofiber dispersion to produce olefin-based composites: ecological and economic viability and industrial practicability are often neglected due to lack of innovation in cleaner production processes. In this context, a low-energy process, which is economically attractive and free of harmful organic solvents, was developed to achieve homogeneous distribution of nanofibrillated cellulose (NFC) in high-density polyethylene (HDPE). The dual interfacial role of the ethylene vinyl alcohol copolymer (EVAL – 48 mol% ethylene content) enhanced interfacial adhesion through the formation of nanobridges between HDPE and NFC. This method led to well-dispersed NFC in the HDPE, at 5 wt% NFC concentration, without the need of any chemical modification, solvent exchange or freeze-drying of NFC. The low interfacial tension between HDPE and EVAL and the presence of NFC in the ternary system led to enhanced dispersion during melt-mixing. Improvement in mechanical properties was achieved, with a 22% and 98% increase in the tensile strength and Young's modulus, respectively, without significantly compromising thermal stability and barrier properties. The results shown in this study indicate a significant potential to replace synthetic and costly reinforcement additives while making nanofiber-reinforced flexible composites more sustainable and mechanically robust. In this context, a paradigm shift from fossil-based production technology to a cleaner production strategy such as those exemplified in this study will help achieve a circular production economy concept without hindering functionalities.
Keywords: Biomaterial; Cellulose nanofibrils; Clean manufacturing; Composite films ethylene vinyl alcohol; Nano-slurry; Polyethylene; Sustainability